An Analytical Study Of Annarasa To Maintain Sharira Dhatu by Agni - Bhatnagar, Sanjay Kumar; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurveda "Sarvamdravyam Panchabhautikam" i.e all creation arises out of five great elements known as Mahabhutas. As per Ayurvedic theory, like all the universal matter our body is also formed by the Pancha Mahabhutas. In this Panchabautika Sharira Various Paka (metabolic transformations) are going on continuously. [1] Agni is the invariable agent in the process of Paka (digestion, transformation). Ingested food is to be digested, absorbed and assimilated, which is unavoidable for the maintenance of life, and is performed by the Agni. Different examples are available in our classics to indicate that Pitta is the same as Agni, but some doubt arises behind this concept, that Pitta is Agni. Agni is innumerable because of its presence in each and every Paramanu of the body. But, the enumeration of the number of Agni varies in various classical Ayurvedic texts. According to the functions and site of action, Agni has been divided into 13 types, i.e.one Jatharagni, five Bhutagni and seven Dhatvagni. Jatharagni is the most important one, which digests four types of food and transforms it into Rasa and Mala.[2] In these sequences, the term Agni comprehends various factors which participates and regulate the course of digestion and metabolism. The paper tries to validate this theory scientifically.